Computational Stylistics in Poetry, Prose, and Drama - Bories, Anne-Sophie; Plecháč, Petr; Fabo, Pablo Ruiz (De Gruyter, 2022)
The contributions in this edited volume approach poetry, narrative, and drama from the perspective of Computational Stylistics. They exemplify methods of computational textual analysis and explore the possibility of computational generation of literary texts. The volume presents a range of computational and Natural Language Processing applications to literary studies, such as motif detection, network analysis, machine learning, and deep learning.